2019
DOI: 10.1111/jcmm.14807
|View full text |Cite
|
Sign up to set email alerts
|

Cistanches alleviates sevoflurane‐induced cognitive dysfunction by regulating PPAR‐γ‐dependent antioxidant and anti‐inflammatory in rats

Abstract: This study aimed to investigate the protective effects and underlying mechanisms of cistanche on sevoflurane-induced aged cognitive dysfunction rat model. Aged (24 months) male SD rats were randomly assigned to four groups: control group, sevoflurane group, control + cistanche and sevoflurane + cistanche group. Subsequently, inflammatory cytokine levels were measured by ELISA, and the cognitive dysfunction of rats was evaluated by water maze test, open-field test and the fear conditioning test. Three days foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
(160 reference statements)
2
23
0
Order By: Relevance
“…The appropriate management of pre-existing diseases and maintenance of optimum bodily functioning may be an effective way to reduce the incidence of sevoflurane-induced POCD. Finally, in older animals, postanaesthetic sevoflurane-related behavioral deficits tend to be larger and last longer than those in younger animals ( Peng et al, 2020 ).Therefore, it is important that studies include aged rodents when performed to investigate the mechanism of sevoflurane-induced POCD.…”
Section: Sevoflurane-inhalation Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate management of pre-existing diseases and maintenance of optimum bodily functioning may be an effective way to reduce the incidence of sevoflurane-induced POCD. Finally, in older animals, postanaesthetic sevoflurane-related behavioral deficits tend to be larger and last longer than those in younger animals ( Peng et al, 2020 ).Therefore, it is important that studies include aged rodents when performed to investigate the mechanism of sevoflurane-induced POCD.…”
Section: Sevoflurane-inhalation Anesthesiamentioning
confidence: 99%
“…Cistanches . can regulate PPAR-γ-dependent antioxidative and anti-inflammatory effects in rats ( Peng et al, 2020 ). Both resveratrol and Cistanches have been proven to reduce sevoflurane neurotoxicity in rats.…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…In recent years, some reports suggested that Sev could induce neuronal apoptosis and the resulting neurotoxicity is attributed to cognitive impairment like POCD in the elderly animal models [ 1 , 9 , 10 ]. In addition, a few researches showed that reactive oxygen species (ROS) and neuroinflammation [ 11 , 12 15 ] were closely related to the pathogenesis of POCD. Despite more than 20 years of intensive research and the fact that some signaling pathways were discovered, most details and exact mechanisms about POCD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has confirmed that PPARγ possessed potent effects of anti-inflammatory and antioxidative 32 , 33 . Thus, we speculated that PPARγ related to the protective effects of licochalcone A against LPS-induced inflammatory dermal cells.…”
Section: Discussionmentioning
confidence: 89%